LEGAL BASES OF MUNICIPAL GOVERNMENT IN RUSSIA AT THE VERGE OF XVIII-XIX cc. - L. Kuanchaleyeva (Russian Journal of Economics and Law, 2008)
The article is dedicated to the analysis of administrative-legal bases of the municipal government reorganization in Russia at the verge of XVIII-XIX cc. Viewing the largest administrative-legal acts of Paul I reign, dedicated to the municipal government reorganization, the author revealed the logic and principles of administrative-legal reform of that epoch and showed the features of its realization with the example of municipal government reorganization.